Deciphering the biodiversity: Production mutualism in the global food security debate - Seppelt, Ralf; Arndt, Channing; Beckmann, Michael; Martin, Emily A.; Hertel, Thomas W. (Elsevier, 2020)
Increasing demands for agricultural commodities are resulting in more intensely managed landscapes. This is at odds with biodiversity conservation and largely ignores farmland biodiversity’s supporting function for high and stable yields. An overhaul of agroeconomic models to account for the biodiversity-production mutualism is urgently needed to answer a question of utmost importance: How do we manage the resources of our planet in such a way that we produce enough healthy food without destroying our life-support system? A comprehensive analytical framework is provided that accounts for multitrophic biodiversity-production processes; bridges disciplinary boundaries between agronomy, agroecology, economics, and conservation science; and elucidates the strong interactions of ecosystem functioning with food security and malnutrition.